A new approach to balancing dental fear and anxiety using BachTM Flower Therapy - Irina Maria Gheorghiu; Alexandru Andrei Iliescu; Stana Păunică; Marina Giurgiu; Brandusa Mocanu; George Alexandru Popescu; Anca Silvia Dumitriu (Journal of Mind and Medical Sciences)
Treatments in dentistry currently consist of an interdisciplinary approach, including (but not necessarily limited to) the holistic perspective. The different fields of allopathic and complementary medicine are used together to ensure not only a high-quality restorative treatment, but also to provide patients with psychological and emotional support. This perspective also applies to dental anxiety, which consists of complex (emotional, vegetative and psychomotor) manifestations. One of the most well-known complementary therapies for reducing dental fear and anxiety is BachTM Flower Therapy. Even if the mechanism of action of this therapy is not yet scientifically documented, notable results have been and continue to be reported in the literature in several clinical studies on patients with dental diseases. It is indicated for both adults and children, in the latter when they go through major biological changes, such as primary and permanent dentition. As a conclusion, BachTM flower therapy is effective and complementary to dental treatments applied to patients, by reducing stress, anxiety, as well as creating a climate of peace, trust and confidence, both for the patient and the doctor. In addition, it is a relatively accessible and cheap form of care, with no significant adverse effects noted so far.